2022
DOI: 10.1249/mss.0000000000002973
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Sleep and Nonwear in 24-h Wrist Accelerometer Data from the National Health and Nutrition Examination Survey

Abstract: Estimating physical activity, sedentary behavior, and sleep from wrist-worn accelerometer data requires reliable detection of sensor nonwear and sensor wear during both sleep and wake. Purpose: This study aimed to develop an algorithm that simultaneously identifies sensor wake-wear, sleep-wear, and nonwear in 24-h wrist accelerometer data collected with or without filtering. Methods: Using sensor data labeled with polysomnography (n = 21) and directly observed wake-wear data (n = 31) from healthy adults, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although the SWaN algorithm developers have demonstrated that their algorithm performs similarly to or better than several popular nonwear and sleep detection methods, both training and validation datasets were comprised of several disparate datasets, each with small sample sizes (<31 participants) of healthy, young participants (mean ages, 18.8–23.8 yr) (24). Additionally, data from a variety of activity monitors (Axivity, ActiGraph GT9X and GT3X+) were used, and the target classes within the datasets were unbalanced and blended from multiple sources to achieve a training dataset with all three labeled behavior classes (sleep wear, wake wear, and nonwear) (24). Thus, additional independent validation of the SWaN algorithm against ground-truth observation of all classified behaviors (wake wear, sleep wear, and nonwear) in a single dataset collected in a broader population would likely enable a better definition of confidence limits surrounding our observations of nonwear and wear fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the SWaN algorithm developers have demonstrated that their algorithm performs similarly to or better than several popular nonwear and sleep detection methods, both training and validation datasets were comprised of several disparate datasets, each with small sample sizes (<31 participants) of healthy, young participants (mean ages, 18.8–23.8 yr) (24). Additionally, data from a variety of activity monitors (Axivity, ActiGraph GT9X and GT3X+) were used, and the target classes within the datasets were unbalanced and blended from multiple sources to achieve a training dataset with all three labeled behavior classes (sleep wear, wake wear, and nonwear) (24). Thus, additional independent validation of the SWaN algorithm against ground-truth observation of all classified behaviors (wake wear, sleep wear, and nonwear) in a single dataset collected in a broader population would likely enable a better definition of confidence limits surrounding our observations of nonwear and wear fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…A three-step, open-source algorithm (24) was used to classify each minute of PAM data as nonwear, sleep wear, wake wear, or unknown. The algorithmically scored wear classifications were applied before the NCHS data release, with greater detail on how the algorithm handled ISM and made predictions of the target classes provided elsewhere (24).…”
Section: Methodsmentioning
confidence: 99%
“…These devices will be worn on the non-dominant wrist. Wrist sensor data will be processed using Monitor-Independent Movement Summary unit (MIMS) to yield overall movement volume estimations [ 40 ] and machine learning algorithms to yield sensor wear, sleep, and wake behavior characterization (i.e., sedentary, ambulation, and upright behaviors) [ 41 , 42 , 43 , 44 ] during the 16-week intervention period. (ii) Health outcomes : (a) anthropometrics (height, weight, and waist/hip circumference); (b) body composition (via bioelectrical impedance) [ 45 ]; (c) seated resting heart rate and blood pressure; (d) fasting blood biomarkers (blood glucose and lipid profile); (e) cognition (via The NIH Toolbox Cognition Battery) [ 46 ]; (f) physical function (via The Short Physical Performance Battery) [ 47 , 48 ]; (g) upper and lower body muscle endurance (via maximal push-up and squat tests, respectively) [ 49 ]; (h) aerobic fitness (via the six-minute walk test) [ 50 , 51 ]; and (i) other questionnaire-based health outcomes (see supplementary study protocol ).…”
Section: Methodsmentioning
confidence: 99%
“…(iii) Motion data will be extracted from Centrepoint and processed on our backend located on Northeastern University’s high-performance computing cluster. This backend includes signal visualization software (i.e., Signaligner Pro v2.3.10-beta; Signaligner.org) [ 42 ], a signal quality control (QC) algorithm to identify anomalous sensor signals [ 75 ] that are unrepresentative of human movement, motion summarization algorithms for total activity volume (i.e., MIMS) [ 40 ], and activity classification using machine learning algorithms: (a) SWaN (sleep, wear, and non-wear) [ 44 ] and (b) MUSS (i.e., multi-site sensing for activity recognition: lying, sitting movement, non-wear, ambulation, and upright movement) [ 41 , 43 ]. The three algorithmic outputs are up sampled to an event resolution of one second and paired with a composite SWaN plus MUSS prediction ( Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation